The Marriage Dispensation Paradox: The Increase in Early Marriages Following the Revision of the Marriage Law in Probolinggo - Khoir , Nasrul; Rizal, Sofian Syaiful (International Journal of Islamic Thought and Humanities, 2025)
The phenomenon of early marriage in Probolinggo Regency has increased despite the enactment of Law Number 16 of 2019, which raised the minimum marriage age for women from 16 to 19 years, aligning it with men's legal age. This rise is especially notable in rural and coastal areas, posing serious child protection challenges. This study employs a normative juridical approach, analyzing legislation, marriage dispensation records from the Probolinggo Religious Court, and interviews with officials from religious and community institutions, as well as families involved in early marriages. The findings reveal inconsistent and weak enforcement of marriage dispensation regulations, which undermine the law’s effectiveness. Moreover, persistent socio-cultural norms that favor early marriage, economic hardship, low educational attainment, and family pressures contribute significantly to the continuation of early marriages. Early marriage is often motivated by concerns about premarital pregnancy, social stigma, and economic factors. To address these challenges, the study recommends more vigorous enforcement of dispensation procedures, alongside improving educational and economic opportunities for families. It also calls for enhanced cross-sector collaboration among government bodies, community leaders, and civil society. These integrated measures are essential to effectively reducing early marriage rates and improving child protection in Probolinggo Regency.